Sirkulasi virus Avian influenza H5N1 Tahun 2010 : Virus genetic drift mirip A/Ck/West Java/Pwt-Wij/2006 ditemukan di beberapa kabupaten di Sumatra dan Jawa - Dharmayanti, NLP Indi; Ratnawati, Atik; Hewajuli, Dyah Ayu; Indriani, Risa (Perhimpunan Biologi Indonesia, 2012)
The avian influenza H5N1 virus circulation in 2010 : Genetic Drift Like Virus A/Chicken/West Java/Pwt-Wij/2006 was found in several districts of Sumatra and Java. Until 2011, the H5N1 subtype of AI virus is still circulating in many parts of Indonesia. The discovery of the AI viruses which have undergone genetic drift since 2006 until now requires serious attention from the government in terms of AI disease control, the surveillance and monitoring of virus circulation and execution of genetic mapping to determine the genetic character of the AI virus at the molecular level, especially on the surface of glycoproteins (HA and NA protein).This information is needed to determine the diversity and character of the AI virus in Indonesia. Genetic data are used to evaluate the strategy to control AI in Indonesia, such as vaccination and the vaccine seed used and determine the extent of AI virus mutation in Indonesia has beenmutated. This study conducted by monitoring of the AI virus circulation throughout 2010. The methods used were AI virus isolation, RT-PCR, sequencing of genes coding for viral surface and the prediction of three-dimensional analysis to determine the location of virusmutation. The results of this study showed that most of the AI virus subtype H5N1, which was isolated during the year 2010, showed similar mutations to the genetic drift virus in 2006, A /Ck/West Java/Pwt-Wij/2006. The viruses were characterized by the presence of 18-19 amino acid substitutions at the level of the HA protein. On the NA protein level, there is a single mutation which was buried in the NA molecule. This mutation probably did not influence for NA activity. Genetic mapping of AI virus subtype H5N1 in 2010 showed that the viral genetic driftas the mutan virus A/Ck/West Java/Pwt-Wij/2006 have circulated not only in West Jawa alone but has been found on the island of Sumatra, Banten, West Jawa and East Jawa.Keywords: Circulation, avian influenza H5N1 virus, genetic drift